2010
DOI: 10.1021/nn901916m
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Carbon Supercapacitors in an Ionic Liquid: A Computer Simulation Study

Abstract: Supercapacitors composed of carbon nanotube (CNT) micropores in the room-temperature ionic liquid (RTIL) 1-ethyl-3-methylimidazolium tetrafluoroborate (EMI+BF4(-)) are studied via molecular dynamics (MD)computer simulations. It is found that the distribution of RTIL ions inside the micropore varies significantly with the pore size. Internal solvation of small (6,6) and (7,7) CNTs with an electrified interior wall is effected almost exclusively via counterions. Surprisingly, these counterions, even though they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
307
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(319 citation statements)
references
References 53 publications
12
307
0
Order By: Relevance
“…Although it was observed from experiments and some simulations that the best performances were obtained for CDCs with an average pore size matching the size of the ions [24][25][26][27][28] , in a recent theoretical study, Kondrat et al 29 have shown that the best average pore size depends on the operating voltage. Nevertheless their model was based on a description of the porous carbon based on a distribution of slit-like pores; the present results show that it would be necessary to inject a more detailed adsorption model to fully address this point.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was observed from experiments and some simulations that the best performances were obtained for CDCs with an average pore size matching the size of the ions [24][25][26][27][28] , in a recent theoretical study, Kondrat et al 29 have shown that the best average pore size depends on the operating voltage. Nevertheless their model was based on a description of the porous carbon based on a distribution of slit-like pores; the present results show that it would be necessary to inject a more detailed adsorption model to fully address this point.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the PZC in our simulations corresponds to neither a minimum nor a maximum in DC. While simple EDL theories predict a minimum in DC at PZC, experimental measurements of DC 35,40 clearly show that the position of the minimum or maximum in DC depends upon the particular system and often does not correspond to PZC.…”
Section: B Capacitancementioning
confidence: 94%
“…Previously, it was observed that the best performance of SCs can be realized when the average micropore size in nanostructured bulk electrodes (e.g., carbide-derived carbon) matches the size of the ions in the electrolyte [8][9][10][11][12][13][14][15] . It is expected that such a resonant effect is true even for defect-induced pores in quasi-two dimensional FLG substrates ( Figure 1a).…”
Section: Identification Of Best-suited Electrolytementioning
confidence: 99%